The role of astrocytes in Alzheimer’s disease: a bibliometric analysis - An, Xiaoqiong; He, Jun; Bi, Bin; Wu, Gang; Xu, Jianwei; Yu, Wenfeng; Ren, Zhenkui (Frontiers in Aging Neuroscience, 2024)
BackgroundAlzheimer’s disease (AD) is a neurodegenerative disorder marked by cognitive decline and memory loss. Recent research underscores the crucial role of astrocytes in AD. This study reviews research trends and contributions on astrocytes in AD from 2000 to 2024, shedding light on the evolving research landscape.MethodsWe conducted a bibliometric analysis using data from the Web of Science Core Collection, covering publications from January 1, 2000, to July 6, 2024, on “Alzheimer’s disease” and “astrocytes.” We identified 5,252 relevant English articles and reviews. For data visualization and analysis, we used VOSviewer, CiteSpace, and the R package “bibliometrix,” examining collaboration networks, co-citation networks, keyword co-occurrence, and thematic evolution.ResultsBetween 2000 and 2024, 5,252 publications were identified, including 4,125 original research articles and 1,127 review articles. Publications increased significantly after 2016. The United States had the most contributions (1,468), followed by China (836). Major institutions were the University of California system (517) and Harvard University (402). The Journal of Alzheimer’s Disease published the most articles (215). Verkhratsky A was the top author with 51 papers and 1,585 co-citations.ConclusionOur extensive bibliometric analysis indicates a significant increase in research on astrocytes in AD over the past 20 years. This study emphasizes the growing acknowledgment of astrocytes’ crucial role in AD pathogenesis and points to future research on their mechanisms and therapeutic potential.